Strategies to optimize the biocompatibility of iron oxide nanoparticles - "SPIONs safe by design" - Janko, Christina; Zaloga, Jan; Poettler, Marina; Dürr, Stephan; Eberbeck, Dietmar; Tietze, Rainer; Lyer, Stefan; Alexiou, Christoph (Journal of Magnetism and Magnetic Materials, 2017)
Various nanoparticle systems have been developed for medical applications in recent years. For constant improvement of efficacy and safety of nanoparticles, a close interdisciplinary interplay between synthesis, physicochemical characterizations and toxicological investigations is urgently needed. Based on combined toxicological data, we follow a safe-by design strategy for our superparamagnetic iron oxide nanoparticles (SPION). Using complementary interference-free toxicological assay systems, we initially identified agglomeration tendencies in physiological fluids, strong uptake by cells and improvable biocompatibility of lauric acid (LA)-coated SPIONs (SPIONLA). Thus, we decided to further stabilize those particles by an artificial protein corona consisting of serum albumin. This approach finally lead to increased colloidal stability, augmented drug loading capacity and improved biocompatibility in previous in vitro assays. Here, we show in whole blood ex vivo and on isolated red blood cells (RBC) that a protein corona protects RBCs from hemolysis by SPIONs. (C) 2016 Elsevier B.V. All rights reserved.
EVALuna2:33179